The Effects of Infusion of Thrombin or Endotoxin in Rabbits Treated with Cortisone - Stafford, Benjamin T; Rapaport, Samuel I; Shen, Stephen M.-C (Thrombosis and Haemostasis, 1975)
Rabbits treated for 4 days with cortisone to prepare for the generalized Shwartzman reaction (GSR) were infused with thrombin or endotoxin. Whereas endotoxin induced the GSR, infusion of from 120-400 U/kg of thrombin over 1 to 2½ hr failed to induce the GSR. Mean values for fibrinogen consumption after thrombin or endotoxin, calculated from changes in plasma fibrinogen concentration and plasma 125I-fibrinogen radioactivity, were as follows: for rabbits infused with thrombin, from 43 to 61 mg/kg over a 3 hr period; for rabbits infused with endotoxin, 58.5 mg/kg over a 6 hr period. A small peak of non-clottable protein radioactivity, indicative of secondary fibrinolysis, was found in animals infused with thrombin but not in animals infused with endotoxin. A striking late rise in plasma fibrinogen levels was noted in animals infused with endotoxin. It was not noted in animals infused with thrombin. This observation provides further evidence that endotoxin stimulates fibrinogen synthesis by mechanisms independent of intravascular clotting or fibrinolysis. The failure to produce the GSR with thrombin in cortisone-treated rabbits leads us to conclude that depression of reticuloendothelial cell clearance of fibrin can not account for the preparatory effect of cortisone for the GSR after endotoxin.